Menggali Konsep Inklusi Dalam Al-Qur'an: Implikasinya Bagi Pendidikan Modern - Wijaksono, Agung; Hartono, Hartono (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
This study aims to explore the concept of inclusion in the Qur'an and examine its implications for the development of a more holistic and equitable modern education system. Inclusive education is often understood in the context of accessibility and equal opportunities, yet the Qur'an offers a more comprehensive approach, emphasizing social justice, appreciation of diversity, and the formation of spiritual character. The inclusive values in the Qur'an implicitly teach a balance between moral, spiritual, and intellectual aspects within the educational process. The study focuses on two primary objectives: first, to identify the principles of inclusion in the Qur'an; and second, to integrate these principles into the framework of modern education. The research employs a qualitative method with a thematic interpretation (maudhu'i) of Qur'anic verses related to inclusion, supported by a hermeneutic approach to understand the text's meaning in the context of contemporary education. The findings indicate that inclusion in the Qur'an not only refers to physical equality or learning opportunities but also to efforts in shaping individuals with strong social responsibility, spiritual awareness, and a deep sense of justice. The concepts of piety, respect for diversity, and social justice serve as relevant foundations for application in the current education system. These findings offer a new, significant perspective for formulating more inclusive educational policies based on Islamic spiritual and ethical values.